Effects of Turbulators on an airfoil at low Reynolds number in turbulent flow - Delnero, Juan Sebastián (2007)
The objective of this work is the study of the effect of different configurations of turbulators as flow control devices, when an airfoil is immersed in a flow that reproduces the natural turbulent characteristics of the low atmospheric boundary layer. The efficiency of an Eppler 387 airfoil modified with several configurations of turbulators is studied. The tests were performed in a boundary layer wind tunnel using an aerodynamic balance and smoke for flow visualizations.